Somes problems in the identification of elastic beam by the dynamical characteristics - Khiem, Nguyen Tien (Vietnam Journal of Mechanics, 1995)
Two problems in the identification of Mechanical system are presented and solved by the analytical method. Firstly, the length of an elastic beam is found from measured natural frequencies. Secondly, the boundary condition of the beam was also obtained with given frequencies. In both the cases, unique solution can be found only with condition, that is given in this paper.